PELAKSANAAN PERATURAN WALIKOTA PEKALONGAN NOMOR 35 TAHUN 2010 TENTANG SISTEM DAN PROSEDUR PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN SERTA PERMASALAHANNYA DI KOTA PEKALONGAN - Ikayanti Ikayanti; Jawade Hafidz (Jurnal Akta, 2017)
One of the taxes levied by the district/city government is the right to land and buildings (BPHTB). Implementation in Pekalongan City based on Pekalongan Perwal No. 35 of 2010. As done in the implementation of Pekalongan Perwal No. 35 of 2010 in processed is a mandatory dishonesty, so that checks the location of objects subject to BPHTB and for taxpayers can not be given and adjusted with compulsory conditions tax.Keywords : Mayor Regulation and Customs Acquisition of Land and Building Rights